Migration Between Europe and North Africa and the Hybridization of Urban and Domestic Practices - (:unkn) unknown (My University, 1992)
Much of what has been written about North African immigration in Europe focuses on policies of integration and their effects, and on problems experienced by North African subjects in the areas of employment, training, urban life, and civil rights in the host country. It may be interesting, also, to study the cultural evolutions of these migrants, looking at the nature of the exchanges that take place between one society to another, and the marks left by these exchanges on the subjects themselves, or, more precisely, on their domestic universe, and on their relationship to the public space. This is what we propose to do in this article.
Keywords: African Research